A framework for classifying patient safety practices: results from an expert consensus process. Issue 7 (24th May 2011) - Dy, Sydney M; Taylor, Stephanie L; Carr, Lauren H; Foy, Robbie; Pronovost, Peter J; Øvretveit, John; Wachter, Robert M; Rubenstein, Lisa V; Hempel, Susanne; McDonald, Kathryn M; Shekelle, Paul G
Abstract : Objective: Development of a coherent literature evaluating patient safety practices has been hampered by the lack of an underlying conceptual framework. The authors describe issues and choices in describing and classifying diverse patient safety practices (PSPs). Methods: The authors developed a framework to classify PSPs by identifying and synthesising existing conceptual frameworks, evaluating the draft framework by asking a group of experts to use it to classify a diverse set of PSPs and revising the framework through an expert-panel consensus process. Results: The 11 classification dimensions in the framework include: regulatory versus voluntary; setting; feasibility; individual activity versus organisational change; temporal (one-time vs repeated/long-term); pervasive versus targeted; common versus rare events; PSP maturity; degree of controversy/conflicting evidence; degree of behavioural change required for implementation; and sensitivity to context. Conclusion: This framework offers a way to classify and compare PSPs, and thereby to interpret the patient-safety literature. Further research is needed to develop understanding of these dimensions, how they evolve as the patient safety field matures, and their relative utilities in describing, evaluating and implementing PSPs.